Trade, recycling and mixing in local metal management strategies of the later Bronze Age south Carpathian Basin: lead isotope and chemical analyses of hoarded metalwork - Bruyère, Caroline; Daly, J. Stephen; Acken, David van; Jovanović, Dragan; Orfanou, Vana; Franković, Filip; Spasić, Miloš; Koledin, Jovan; Molloy, Barry P. C. (Journal of archaeological science, 2024)
Lead Isotope Analysis (LIA) has been applied most often as a means of provenancing copper at the macro scale. Here we use LIA at the regional scale to expose the relationship between long-distance communication and local metal management strategies. We conducted lead isotope and chemical analysis on 82 objects and ingots from Late Bronze Age hoards of the south Carpathian Basin, a node in long distance networks. From a social perspective, results indicate the presence of a community of practice of metalworkers that went beyond socio-political boundaries. Analyses of ingots demonstrate that communities imported copper from a variety of distant sources, but local circulation and specific mixing and recycling practices created a characteristic chemical signature unique to this region. Moreover, metalworkers' choices of copper sources were tailored to specific object types. From an analytical perspective, we demonstrated that the frequent mixing of copper from different sources with varying lead concentrations to make objects resulted in the masking of LIA signatures for some sources - we termed these ‘ghost fractions’ in mixtures - by others with more lead.
Online veröffentlicht am 6. März 2024
Gesehen am 29.10.2024